Jealous Missionaries on the Pacific Northwest Coast of Canada. (21st April 2015) - Brock, Peggy
Abstract : Most of our knowledge of missions and missionary interactions with the indigenous peoples they evangelised comes from the missionaries' own writings, mainly correspondence and reports to the home society. Rarely do we find an indigenous view of missionaries. In this article I will consider one of these unusual perspectives, the diary of a Tsimshian from the northwest coast of British Columbia, Arthur Wellington Clah, who became a Christian and interacted with several missionaries over many years while retaining independence from missionary oversight. Clah's view of missionaries forms a counterpoint to missionary representations of their own role in religious change. He makes judgments about missionaries' morals and probity, many of which are based on Christian principles learned from the missionaries themselves, while also being informed by Tsimshian values and modes of interaction. The various influences on Clah will be considered through the prism of his use of the descriptor "jealous" as he applied it to his missionary acquaintances. The analysis of his commentary on missionary behaviour and emotions becomes an investigation of cross‐cultural communication and understanding.